2003
DOI: 10.1001/archneur.60.9.1223
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography of Striatal Serotonin Transporters in Parkinson Disease

Abstract: These results suggest that the density of serotonin transporters, like that of dopamine transporters, is reduced in the striatum of patients with PD and that these changes are related to disease stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 42 publications
(52 reference statements)
10
97
1
Order By: Relevance
“…The mean ISI coefficient of variation (0.52±0. 18) was significantly lower than the value in normal rats (P < 0.05; Fig. 4).…”
Section: Resultsmentioning
confidence: 69%
“…The mean ISI coefficient of variation (0.52±0. 18) was significantly lower than the value in normal rats (P < 0.05; Fig. 4).…”
Section: Resultsmentioning
confidence: 69%
“…In basal ganglia, for example, 5-HT exerts a phasic inhibitory control over GABA synthesis and release [36]. Parkinson patients display a reduced level of striatal serotonin binding sites [30] and transporters [92]; accordingly, the selective 5-HT uptake inhibitor citalopram, associated to L-DOPA treatment, was reported to alleviate both bradykinesia and depressive symptoms [34,156]. Therefore, a more detailed investigation for the precise role of 5-HT receptors controlling GABA-mediated transmission in basal ganglia might offer new perspectives in the therapy of Parkinson disease.…”
Section: Role In Motor Controlmentioning
confidence: 99%
“…Reduced brain levels of all of the key markers for the 5-HT neurotransmitter system provide compelling evidence for a striatal serotonergic abnormality in PD. This evidence has been confirmed by antemortem studies and imaging investigations that showed reduced cerebrospinal fluid levels of 5-HIAA and decreased activity of 5-HTT not only in the caudate nucleus and the putamen but also in the thalamus and medial frontal areas, indicating a pathophysiological involvement of 5-HT in PD (Haapaniemi et al, 2001;Kerenyi et al, 2003;Kim et al, 2003). It is, however, very likely that the degree of serotonergic degeneration depends on the stage of the disease .…”
Section: -Ht In Pd and Other Motor Disordersmentioning
confidence: 78%